(untitled) (Global Journal of Human-Social Science, 2013)
Transportation in Lagos State, Nigeria is a major challenge that over the years had called for serious attention. Every attempt at solution seems to compound it. We conducted a review of the literature in the area of BRT systems to identify and subsequently classify their major aspects, and determine their linkages and trade-offs. Also, we developed from a theoretical point of view the basis of the BRT deployment planning framework, followed by collecting the necessary data to exercise the framework in the context of a site-specific case study (Lagos State). We adopted a system optimization approach in order to assist transit agency to decide on optimal deployment strategy to employ. The study reveals that the deployment of BRT systems relative to an array of factors ranging from large, small and sitespecific cases among other things do not only ameliorate the challenge of transportation but also in a way attempted to do justice to the first MDG agenda of attainment of low-pollution Green House Gases (GHG). Also, reveals that ticketing system needs a radical approach to curb timeloss occasioned by validation of purchased tickets.